Pengendali Lampu dan Kipas Angin Dari Jarak Jauh Dengan Wifi dan Raspberry Pi - Hermawan, Deny; , Helman Muhammad, S.T., M.T (2017)
Each lecture activity conducted in every classroom within FKI UMS always uses electronic equipments, among them are lampsand fans. Based on observations, many of those equipments were used inefficiently where most of the time they were still turned on despite being not in use anymore. This fact raised motivation to develop a system for controlling lamps and fans remotely via smartphone with web page as user interface.The course of this research followed the stages defined in the prototyping method.UMS Wifi network was used as the communications infrastructure, andRaspberry Piwas used as the controller device. Relays were connected to the Raspberry Pi through GPIO pin, and were used as switching devices for the controlled lamps and fans. Apache web server was installed onthe Raspberry Pi,which made it accessible through web browser resided in the smartphone. From the test results, the maximumalloweddistance between the smartphone and the Raspberry Pi was9 meters. All the buttons on the web page have been working accordingto the desired functions. The success rate reached 100% after 10 times experiment.